2013
DOI: 10.1002/ange.201306541
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper‐Catalyzed Conjugate Addition of Trimethylaluminum to β,γ‐Unsaturated α‐Ketoamides: Efficient Access to γ‐Methyl‐Substituted Carbonyl Compounds

Abstract: Vollständig regioselektiv reagieren β,γ‐ungesättigte α‐Ketoamide bei der Umsetzung mit Trimethylaluminium zu den 1,4‐Addukten, die in guten bis ausgezeichneten Ausbeuten und Enantioselektivitäten erhalten werden. Der Aufbau γ‐methylierter Carbonylmotive – Schlüsselbausteine in vielen Naturstoffen – zeigt die Anwendungsmöglichkeiten des Verfahrens in der Synthese. Binap=2,2′‐Bis(diphenylphosphanyl)‐1,1′‐binaphthyl, TC=Thiophencarboxylat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Alexakis et al. used the highly reactive AlMe 3 as the Michael donor to achieve a remarkable Cu‐catalyzed asymmetric 1,4‐addition to β,γ‐unsaturated α‐ketoesters,8a as well as β,γ‐unsaturated α‐ketoamides 8b. However, these substrates are particularly challenging for rhodium‐catalyzed asymmetric conjugate additions, owing to the high reactivity of the α‐keto moiety, which promotes 1,2‐addition 9.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alexakis et al. used the highly reactive AlMe 3 as the Michael donor to achieve a remarkable Cu‐catalyzed asymmetric 1,4‐addition to β,γ‐unsaturated α‐ketoesters,8a as well as β,γ‐unsaturated α‐ketoamides 8b. However, these substrates are particularly challenging for rhodium‐catalyzed asymmetric conjugate additions, owing to the high reactivity of the α‐keto moiety, which promotes 1,2‐addition 9.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that chiral sulfinylphosphine ligands effectively promoted Rh‐catalyzed arylation of arylboronic acids to nitro‐styrenes and chalcones, and provide chiral gem ‐diarylalkanes in high yield and enantiomeric excess 10. To examine the feasibility of this strategy, phenylboronic acid 2 a was added to the β,γ‐unsaturated α‐ketoamides ( 1 a – c )8b and ligand L1 11 with [{Rh(C 2 H 4 ) 2 Cl} 2 ] as catalyst, in the presence of aqueous KOH in dichloromethane (DCM) at 40 °C (Table 1, entries 1–3). Amides ( 1 a – c ) provide the 1,4‐adduct 3 as product in more than 86 % yield with excellent 1,4‐selectivity (93/7 to 94/6) and enantioselectivities (92–93 % ee ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations